Penyerangan Terhadap Warga Sipil Oleh Organisasi Papua Merdeka Dan Pertanggungjawabannya - Ririhena, Putri Jean Patricia; Tahamata, Lucia Charlota Octovina; Leatemia, Wilshen (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2025)
Introduction: the armed conflict in Papua is one of the most complex humanitarian and security issues in Indonesia. The involvement of the Free Papua Movement (OPM) in attacks on civilians has resulted in loss of life and significant losses, both material and moral. These actions are not merely political resistance but have gone beyond the pale, targeting those who should be protected by law: civilians not participating in hostilities.Purposes of the Research: : the purpose of this article is to determine and analyze whether the acts of attacks on civilians carried out by the Free Papua Organization (OPM) can be qualified as violations of International Humanitarian Law (IHL).Methods of the Research: The method used is normative juridical, employing a legislative approach, a case approach, a historical approach, a conceptual approach, and a literature study approach.Results / Findings / Novelty of the Research: : the results of the study show that the attacks on civilians by the Free Papua Organization (OPM) constitute a serious violation of International Humanitarian Law (IHL), particularly against the principle of distinction and the principle of proportionality as regulated in the 1949 Geneva Conventions and Additional Protocol II of 1977